Are patients with knee osteoarthritis and patients with knee joint replacement as physically active as healthy persons? - Daugaard, Rikke (J Orthop Translat, 2018)
BACKGROUND: It is well documented that patients with knee osteoarthritis (KOA) suffer from reduced physical function and that function of the affected knee is improved after knee joint replacement (KJR). However, it remains uncertain whether patients with KOA are less physically active than healthy people and whether patients increase their level of physical activity after surgery to a level comparable with that of healthy people. The aim of this study was to examine whether patients with KOA are less physically active than healthy participants and whether patients who have undergone KJR show an increased activity and achieve the same level of physical activity as healthy participants 5 years postoperatively. METHODS: Fifty-four patients with KOA (29 women; mean age 62 ± 8.6; mean body mass index (BMI) 27 ± 5), 52 patients who had KJR due to KOA 5 years earlier (26 women; mean age 66 ± 7.2; mean BMI 30 ± 5) and 171 healthy participants (76 women, mean age 64 ± 9.7, mean BMI 26 ± 5) were included in this cross-sectional study. The level of physical activity was measured over a mean period of 5.5 days with a triaxial accelerometer mounted on the thigh. Number of daily steps, number of daily short walking bouts of <10 s duration and number of daily transfers from sitting to standing position were recorded. Data were analysed using two sample t tests and were adjusted for age, gender and BMI. RESULTS: Patients with KOA did not differ significantly from healthy participants regarding daily steps (+321, p = 0.50) or daily transfers from sitting to standing (+1.9, p = 0.52) but performed significantly less daily short walking bouts <10 s (−11.9, p = 0.02). Patients after KJR did not differ significantly from healthy participants regarding daily steps (−281, p = 0.60) of transfers from sitting to standing position (−3.2, p = 0.32) but performed significantly less daily short walking bouts <10 s (−21.7, p = 0.001). CONCLUSION: Patients with KOA and KJR showed no significant reduction in number of daily step counts and transfers from sitting to standing position when compared with matched healthy controls. However, the number of short walking bouts was reduced in patients with KOA and by twice as much in patients with KJR. This indicates that KOA and treatment with KJR hardly affect health-related general activity but do affect specific physical activity behaviour potentially indicative of KOA or post-KJR functional limitations. THE TRANSLATIONAL POTENTIAL OF THIS ARTICLE: Activity monitoring with an accelerometer-based method gives insights into health-related general activity levels such as total daily steps and specific parameters such as short walking bouts, which may serve as an objective outcome measure in clinical practice.